ANALISIS DAYA SAING JAVA “A” COCOA DALAM RANGKA MENENTUKAN STRATEGI PEMASARAN - Babun Suharto (Jurnal Pendidikan Akuntansi Indonesia, 2006)
ANALISIS DAYA SAING JAVA “A” COCOA DALAM RANGKA MENENTUKAN STRATEGI PEMASARANPAM anaysis product showed that Java “A” Cocoa product have high competition in the international market. It’s supported by the resources cost ratio (DRCR) : 0,86. It’s mean that, domestic costs to achieve 86% positive different betweem income for tredeable input cost. So, if we want to create income of product sale Rp. 1,00, we only need sacrifice domestic cost Rp. 0,86. Privat Cost Ratio (PCR) : 0,86 to strengthen the statement that Java “A” Cocoa hame high competitive. It mean, to get income of sale Rp. 1,00, we need domestic resources Rp. 0,84. In multiple regression analysis, premium priice as dependent variable, and cost of : fermentation and drainage, sortasion, package, storage, sanitation, and terminal price as independent variables. All independent variables had influence into premium piece, and the partial influence only several independent variable had significant influence toward premium price for each p;antion. Fermantation and drainafe for PTPN XII and Kendang Lembu pantation, sortation for Jatirono plantation, sanitation for Kalitelepak, and Kalikempit. For general, consumer preferention into production Java “A” Cocoa PTPN XII is fermentation and drainage. Kata Kunci : Daya Saing, Strategi Pemasaran  dan Java “A” Cocoa